2022
DOI: 10.3390/biology11111569
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Experimental Whole-Body Burning on Histological Age-at-Death Estimation from Human Cortical Bone and Dental Cementum

Abstract: Whole-body donations (n = 6) were placed in various experimental fire-death scenarios to understand the histological effects of thermal alteration on bones and teeth. Midshaft samples of the femur, 6th rib, and metatarsal were removed from each donor pre- and post-burning to examine histomorphometric differences and test established age-at-death estimation methods. Dental samples were taken post-burning to test the applicability of dental cementum analysis for age-at-death estimation. Significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…However, our "adult" category was broad, obscuring nuance in different age categories. Recent studies have found DOs highest in the 20-to 30-year age group, classified as "adult" in our study, but that DO osteon population density (OPD) decreased after age 30 [34,36]. The increase in DO OPD in juvenile and young adult humans may therefore be attributable to growth and development of peak bone mass, which, once achieved, tends to decline steadily into old age.…”
Section: Plos Onecontrasting
confidence: 43%
See 2 more Smart Citations
“…However, our "adult" category was broad, obscuring nuance in different age categories. Recent studies have found DOs highest in the 20-to 30-year age group, classified as "adult" in our study, but that DO osteon population density (OPD) decreased after age 30 [34,36]. The increase in DO OPD in juvenile and young adult humans may therefore be attributable to growth and development of peak bone mass, which, once achieved, tends to decline steadily into old age.…”
Section: Plos Onecontrasting
confidence: 43%
“…DOs have been posited as a distinguishing feature between human adult and juvenile bone [7,8]. Research indicates an inverse relationship between age and the presence of DOs, with younger individuals having a higher prevalence of DOs [32][33][34], although DOs are still documented in adult human bone [5,6,35,36]. Streeter [37] published a method of aging human juvenile ribs characterizing the presence of linear DOs as indicative of bone from adolescents.…”
Section: Effect Of Age On Do Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…5.2 | Issue 2: Equating bone color with temperature assumes that the temperature of the fire is immediately and universally transferred to the bones in a fleshed body Unlike a furnace working on a small cleaned bone sample, burning a fully intact human body is a messy process in which various portions burn at different times and at different rates (Mavroudas et al, 2022). Temperatures within the fire are variable due to availability of external fuels, ventilation, moisture, and suppression efforts.…”
Section: Issue 1: Equating Bone Color With Temperature Ignores and Un...mentioning
confidence: 99%
“…Unlike a furnace working on a small cleaned bone sample, burning a fully intact human body is a messy process in which various portions burn at different times and at different rates (Mavroudas et al, 2022). Temperatures within the fire are variable due to availability of external fuels, ventilation, moisture, and suppression efforts.…”
Section: Forensic Issues With the Bone Color/fire Temperature Equationsmentioning
confidence: 99%